A deficiency of the link protein Bral2 affects the size of the extracellular space in the thalamus of aged mice - Cicanic, Michal; Edamatsu, Midori; Bekku, Yoko; Vorisek, Ivan; Oohashi, Toshitaka; Vargova, Lydia (Journal of neuroscience research, 2018)
Bral2 is a link protein stabilizing the binding between lecticans and hyaluronan in perineuronal nets and axonal coats (ACs) in specific brain regions. Using the real-time iontophoretic method and diffusion-weighted magnetic resonance, we determined the extracellular space (ECS) volume fraction (α), tortuosity (λ), and apparent diffusion coefficient of water (ADCW ) in the thalamic ventral posteromedial nucleus (VPM) and sensorimotor cortex of young adult (3-6 months) and aged (14-20 months) Bral2-deficient (Bral2-/- ) mice and age-matched wild-type (wt) controls. The results were correlated with an analysis of extracellular matrix composition. In the cortex, no changes between wt and Bral2-/- were detected, either in the young or aged mice. In the VPM of aged but not in young Bral2-/- mice, we observed a significant decrease in α and ADCW in comparison with age-matched controls. Bral2 deficiency led to a reduction of both aggrecan- and brevican-associated perineuronal nets and a complete disruption of brevican-based ACs in young as well as aged VPM. Our data suggest that aging is a critical point that reveals the effect of Bral2 deficiency on VPM diffusion. This effect is probably mediated through the enhanced age-related damage of neurons lacking protective ACs, or the exhausting of compensatory mechanisms maintaining unchanged diffusion parameters in young Bral2-/- animals. A decreased ECS volume in aged Bral2-/- mice may influence the diffusion of neuroactive substances, and thus extrasynaptic and also indirectly synaptic transmission in this important nucleus of the somatosensory pathway.
Keywords: Analysis of Variance; Animals; myši transgenní; novorozená zvířata; Extracellular Matrix Proteins; extracelulární prostor; Aggrecans; extracellular matrix; agrekany; Female; Mice, Transgenic; ženské pohlaví; Extracellular Space; Quaternary Ammonium Compounds; In Vitro Techniques; Aging; difuzní magnetická rezonance; Animals, Newborn; techniky in vitro; Bral2; gangliová stimulancia; Mice; Thalamus; kvartérní amoniové sloučeniny; neurony; messenger RNA; myši; proteiny nervové tkáně; RNA, Messenger; Neurons; diffusion; analýza rozptylu; Nerve Tissue Proteins; Male; extracelulární matrix - proteiny; thalamus; stárnutí; Diffusion Magnetic Resonance Imaging; zvířata; mužské pohlaví; Mice, Inbred C57BL; aging; Ganglionic Stimulants; myši inbrední C57BL; extracellular space